Interpretation of X-ray photoelectron spectra of carbon-nitride thin films: New insights from in situ XPS. (November 2016) - Hellgren, Niklas; Haasch, Richard T.; Schmidt, Susann; Hultman, Lars; Petrov, Ivan
Abstract: We report on angular-resolved x-ray photoelectron spectroscopy (XPS) studies of magnetron sputtered CNx thin films, first in situ (without air exposure), then after air exposure (for time periods ranging from minutes to several years), and finally after Ar ion etching using ion energies ranging from 500 eV to 4 keV. The as-deposited films typically exhibit two strong N1s peaks corresponding to pyridine-like, and graphite-like, at ∼398.2 eV and ∼400.7 eV, respectively. Comparison between in situ and air-exposed samples suggests that the peak component at ∼402–403 eV is due only to quaternary nitrogen and not oxidized nitrogen. Furthermore, peak components in the ∼399–400 eV range cannot only be ascribed to nitriles or pyrrolic nitrogen as is commonly done. We propose that it can also be due to a polarization shift in pyridinic N, induced by surface water or hydroxides. Argon ion etching readily removes surface oxygen, but results also in a strong preferential sputtering of nitrogen and can cause amorphization of the film surface. The best methods for evaluating and interpreting the CNx film structure and composition with ex-situ XPS are discussed.